FSTL1-USP10-Notch1 Signaling Axis Protects Against Cardiac Dysfunction Through Inhibition of Myocardial Fibrosis in Diabetic Mice - Lu, Linhe; Ma, Jipeng; Liu, Yang; Shao, Yalan; Xiong, Xiang; Duan, Weixun; Gao, Erhe; Yang, Qianli; Chen, Shasha; Yang, Jian; Ren, Jun; Zheng, Qijun; et al. (Frontiers in Cell and Developmental Biology, 2021)
The incidence of type 2 diabetes mellitus (T2DM) has been increasing globally, and T2DM patients are at an increased risk of major cardiac events such as myocardial infarction (MI). Nevertheless, the molecular mechanisms underlying MI injury in T2DM remain elusive. Ubiquitin-specific protease 10 (USP10) functions as a NICD1 (Notch1 receptor) deubiquitinase that fine-tunes the essential myocardial fibrosis regulator Notch signaling. Follistatin-like protein 1 (FSTL1) is a cardiokine with proven benefits in multiple pathological processes including cardiac fibrosis and insulin resistance. This study was designed to examine the roles of FSTL1/USP10/ Notch1 signaling in MI-induced cardiac dysfunction in T2DM. High-fat-diet-treated, 8-week-old C57BL/6J mice and db/db T2DM mice were used. Intracardiac delivery of AAV9-FSTL1 was performed in T2DM mice following MI surgery with or without intraperitoneal injection of crenigacestat (LY3039478) and spautin-1. Our results demonstrated that FSTL1 improved cardiac function following MI under T2DM by reducing serum lactate dehydrogenase (LDH) and cardiac fibroblasts apoptosis as well as cardiac fibrosis. Further in vivo studies revealed that the protective role of FSTL1 against MI injury in T2DM was mediated by the activation of USP10/Notch1. FSTL1 protected cardiac fibroblasts (CFs) against DM-MI-induced cardiofibroblasts injury by suppressing the levels of fibrosis markers, and reducing LDH and MDA concentrations in a USP10/Notch1-dependent manner. In conclusion, FSTL1 treatment ameliorated cardiac dysfunction in MI with co-existent T2DM, possibly through inhibition of myocardial fibrosis and apoptosis by upregulating USP10/Notch1 signaling. This finding suggests the clinical relevance and therapeutic potential of FSTL1 in T2DM-associated MI and other cardiovascular diseases.